Landscapes of mobility in Metro Manila’s business districts - Boquet, Yves (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2019)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/6700/5804